Responsive materials as draw agents for forward osmosis desalination - Cai, Yufeng (2016)
Alternative energy-efficient desalination technology is an exciting research field. Forward osmosis (FO) as a novel desalination technology has attracted much attention in that it is driven by chemical potential with low fouling potential and high fouling reversibility. In FO, the draw agent interacts with water forming a draw solution to reduce the water chemical potential, and thus water would automatically permeate through a selective membrane from brackish water to dilute the draw solution. The draw agent should also separate from water in the regeneration process to leave fresh water behind as the final product. In this thesis, I synthesized a series of responsive materials as draw agents, including hydrogels, polymers and (poly) ionic liquids, and studied the importance of balanced FO and regeneration performances. The merit of responsive draw agent is that the regeneration process can be realized with external stimulus, e.g., temperature, instead of solely relying on traditional reverse osmosis that consumes highgrade electrical energy and faces membrane fouling. The purpose of this thesis is to reveal the potential of responsive draw agents to enable FO to desalinate seawater or even brine with energy cost competent to other technologies. Thermally responsive hydrogels, including semi-interpenetrating network hydrogels and polyionic liquid hydrogels, are studied as responsive draw agents in FO desalination. All these hydrogels are designed with both hydrophilicity and hydrophobicity in structures to assume thermosensitivity. The hydrogels can automatically swell and absorb fresh water from brackish water through an FO membrane at temperatures below their lower critical solution temperature (LCST); at temperatures above the LCST, the hydrogels deswell to release the readily available fresh water. This is quite interesting since I realize a desalination process driven by temperature modulation between room temperature and, for example, 40℃. The thermal energy requirement is lower than that of thermal distillation methods since the enthalpy and temperature of responsive draw agent phase separation with water are much lower than those of water vaporization. Although hydrogels are unfortunately found incapable to desalinate seawater, the aim of this thesis is quite clear, which is to utilize low grade thermal energy from industrial waste heat or solar source to completely or at least largely replace the high grade electrical energy consumption in seawater or even brine desalination. A dual responsive polymer is synthesized and studied in order to fulfill this target. The dual responsive polymer can be reversibly switched by introducing and removal of CO2 between a polyelectrolyte state that can generate water flux from seawater, and a thermally responsive state that facilitates regeneration at temperatures above the LCST. Again, a temperature of 50℃ is sufficient to precipitate the majority of polymers, and a nanofiltration process is then employed to polish the water quality with a low hydraulic pressure of only 1.5 bar. Our aim is partially fulfilled since the majority amount of energy input is low grade thermal energy, if regeneration of CO2 is not considered. A group of thermally responsive ionic liquids are found to be able to generate a water flux from 1.6 M NaCl solution, which is almost 3 times the salinity of seawater. Meanwhile, their diluted draw solutions can undergo a liquid-liquid phase separation at 50℃ to generate a sedimentation phase that can be directly reused as draw solution without regeneration, and a supernatant phase with an osmotic pressure of less than 6 bar. The theoretical energy calculation reveals that FO requires only about one fifth of RO‘s electrical energy consumption for seawater desalination (theoretically 1.1 kWh/m3), and the energy cost of FO is much lower than (less than half of) RO owing to the utilization of much cheaper low grade thermal energy. Finally, a proprietary draw agent is studied to be able to concentrate feed solution into a 17 wt% NaCl solution that facilitates ensuing crystallization process for zero-liquid discharge. Combining with a typical seawater RO plant, the energy consumption for brine treatment would be only the electrical energy equal to that of seawater RO, and additional low grade thermal energy associated with temperature modulation between 20 and 50℃. Therefore, FO enabled by responsive draw agents would be a competent desalination technology to challenge RO and thermal distillation methods in seawater and brine treatment.